2024
DOI: 10.1039/d4tc00173g
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the stacking-dependent electronic properties of the 2D ultrathin rare-earth metalloxenes family LnX2 (Ln = Eu, Gd, Dy; X = Ge, Si)

Alexey N. Mihalyuk,
Polina M. Sheverdyaeva,
Jyh-Pin Chou
et al.

Abstract: The studies of electronic effects in reduced dimensionality have become a frontier in nanoscience due to exotic and highly tunable character of quantum phenomena. Recently, a new class of 2D...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
0
0
Order By: Relevance
“…It is characterized by an atomic terbium layer covered by a buckled silicon bilayer, resulting in a TbSi 2 stoichiometry. It should be noted that most trivalent rare earths form very similar silicide monolayers on Si(111), exhibiting very interesting physical properties such as flat-band conditions on n -type silicon , or two-dimensional ferromagnetism. , In a recent theoretical work it was found that the electronic states around the Fermi energy are mostly located around the rare earth atoms and not at the silicide surface, so that dangling bonds should not be present. Thus, it may already be assumed that the reactivity of the silicide surface with adsorbed molecules is sufficiently low enabling an ordered molecular growth.…”
Section: Introductionmentioning
confidence: 99%
“…It is characterized by an atomic terbium layer covered by a buckled silicon bilayer, resulting in a TbSi 2 stoichiometry. It should be noted that most trivalent rare earths form very similar silicide monolayers on Si(111), exhibiting very interesting physical properties such as flat-band conditions on n -type silicon , or two-dimensional ferromagnetism. , In a recent theoretical work it was found that the electronic states around the Fermi energy are mostly located around the rare earth atoms and not at the silicide surface, so that dangling bonds should not be present. Thus, it may already be assumed that the reactivity of the silicide surface with adsorbed molecules is sufficiently low enabling an ordered molecular growth.…”
Section: Introductionmentioning
confidence: 99%